Germination Traits of Millettia Pinnata (L.) in Response to Salinity - Nasrin, Shamima; Hossain, Mahmood; Alam, Rabiul; Rubaiot Abdullah, S. M.; Saha, Sanjoy; Hasan Siddique, Mohammad Raqibul (Global Journal Of Botanical Science, 2016)
Millettia pinnata is a mangrove associates and found to occur in the Sundarbans mangrove forest of Bangladesh. We have examined the effect of salinity on seed germination of this species. Seed germination experiment was conducted with different salinity levels (0 to 35 ppt) at 5 ppt interval. Throughout the experiment Cumulative Germination Percentage (CGP) varied from 73.89% to 27.78% among 0 to 10 ppt and from 17.22% to 4.44% between 15 to 20 ppt salinity. Final germination percentage (FGP) of M. pinnatta seeds varied significantly (p<0.05) among saline treatments and comparatively higher (73.89%) final germination percentage was observed at non saline condition (0 ppt) and germination percentage was sharply decreased to 32.78% and 22.78% for salinity of 5 and 15 ppt salinity respectively, but no germination was observed for higher salinity levels (25 to 35 ppt). Germination Initiation Time (GIT) of seeds varied significantly (p<0.05) among salinity levels. GIT was the lowest (5 days) at 0ppt and highest (10 days) at 20 ppt salinity level. Mean Germination Time (MGT) of seeds didn’t vary significantly (p>0.05) among salinity levels. MGT was the lowest (9 days) at 0ppt and highest (12 days) at 20 ppt salinity level. Germination Index of seeds varied significantly (p<0.05) among salinity levels. GI was the highest (2.60 seed/day) at 0 ppt and lowest (0.12 seed/day) at 20 ppt salinity level. Germination value (GV) of seeds varied significantly (p<0.05) among salinity levels. GV was the highest (30.90%/day2) at 0 ppt and lowest (0.15%/day2) at 20 ppt salinity level. Therefore, we concluded that the salinity is a critical factor for germination of seed and it reduces germination success with increasing salinity either by inhibiting water absorption or by creating ion toxicity on seed.